Dynamic competitive constraint handling for constrained multi-objective optimization - Wei Li; Haoying Li; Ning Yang; Shuling Yang; Ying Huang (Swarm and Evolutionary Computation, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

Cracking characteristics of rock-anchored beam system during construction of underground powerhouse under high in-situ stress and complex rock mass structures: A case study of Yebatan hydropower station - Peiyang Yu; Xiuli Ding; Shuling Huang; Xinhao Zhu; Yang Qin; Jianhua He; Yuting Zhang; Gang Han (Tunnelling and Underground Space Technology, 2026)

DBD synergistic UiO-66/GO-n: A new dawn for efficient defluorination and rapid degradation of fluorine-containing organic pollutants - Yejian Liu; Lijuan Duan; Shuling Fang; Wuming Xie; Qingnan Zeng; Jingyi Huang; Hongyang Cao; Zhiyuan Ma (Process Safety and Environmental Protection, 2026)

Hydrothermal depolymerization of PET microplastics assisted by pyroelectric-induced polarization in BTO/TiO₂ composite - Shuling Shen; Ziwei Feng; Huixin Feng; Zijian Zhang; Tongxin Huang; Zhihong Tang; Xinjuan Liu; Jing Li; Huixin Xiu (Journal of Environmental Chemical Engineering, 2026)

Deformation Characteristics of Surrounding Rock in a Large Underground Opening Under High In Situ Stress and Complex Rock Mass Structures: A Case Study of Yebatan Hydropower Station - Peiyang Yu; Xiuli Ding; Shuling Huang; Peng-Zhi Pan; Yuting Zhang; Jianhua He; Ju He; Gang Han (Rock Mechanics and Rock Engineering, 2026)

A novel numerical analysis method for the stability of sediment void-type energy storage salt cavern and its application in Tai’an, China - Xiaopeng Liang; Xiuli Ding; Wanrui Hu; Hongling Ma; Shuling Huang; Xilin Shi; Rui Cai; Zhen Zeng; Xuan Wang (Tunnelling and Underground Space Technology, 2026)

Electrochemical aptasensor based on Zr-MOF@Ag nanocomposite for the rapid detection of chloramphenicol in honey, milk and lake water - Zhaoyuan He; Chengxiang Fu; Shuling Meng; Jiaqi Luo; Jieke Qiu; Jianing Huang; Xiaoge Duan; Jiakang He; Jinzi Wang; Hailan Chen (Food Chemistry, 2026)

Mechanisms of water-rock interaction and its impact on swelling and crack behavior of argillaceous dolomite in tunnel uplift zones - Zihang Liu; Kang Huang; Shuling Huang; Xianfeng Liu; Fei Yu; Shanxiong Chen; Zhangjun Dai (Bulletin of Engineering Geology and the Environment, 2026)

Phosphorylated Scrophularia ningpoensis polysaccharides mitigate oxidative stress and modulate immunity by regulating the gut microbiota in cyclophosphamide-treated mice - Lufen Huang; Jianan Wang; Litao Wang; Shuling Liu; Xinru Niu; Zhouwen Wu; Kexin Guo; Si Gong; Bowen Wei; Zhaochun Wang; Jianing Mi; Yufeng Liu; et al. (Food Bioscience, 2025)

Study on the deformation and failure mechanism of tertiary water-rich soft rock tunnels based on the moisture migration-fracture coupling model - Kang Huang; Shuling Huang; Xiuli Ding; Yuting Zhang; Dengxue Liu; Zhangjun Dai (Tunnelling and Underground Space Technology, 2025)

Moisture-absorbing expansion and cracking characteristics of central Sichuan red-bed mudstone based on digital speckle correlation method - Kang Huang; Zhangjun Dai; Shuling Huang; Fei Yu; Shichang Li; Kaiwen Tong; Wei Zhang; Shanxiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Correction: A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao; Cong Luo (Rock Mechanics and Rock Engineering, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Ship Trajectory Planning and Optimization via Ensemble Hybrid A* and Multi-Target Point Artificial Potential Field Model - Yanguo Huang; Sishuo Zhao; Shuling Zhao (Journal of Marine Science and Engineering, 2024)
Ship path planning is the core problem of autonomous driving of smart ships and the basis for avoiding obstacles and other ships reasonably. To achieve this goal, this study improved the traditional A* algorithm to propose a new method for ship collision avoidance path planning by combining the multi-target point artificial potential field algorithm (MPAPF). The global planning path was smoothed and segmented into multi-target sequence points with the help of an improved A* algorithm and fewer turning nodes. The improved APF algorithm was used to plan the path of multi-target points locally, and the ship motion constraints were considered to generate a path that was more in line with the ship kinematics. In addition, this method also considered the collision avoidance situation when ships meet, carried out collision avoidance operations according to the International Regulations for Preventing Collisions at Sea (COLREGs), and introduced the collision risk index (CRI) to evaluate the collision risk and obtain a safe and reliable path. Through the simulation of a static environment and ship encounter, the experimental results show that the proposed method not only has good performance in a static environment but can also generate a safe path to avoid collision in more complex encounter scenarios.

The application of multi-point FBG bolt in measuring the excavation damaged zone of underground caverns - Gang Han; Shuling Huang; Xiuli Ding; Yuting Zhang; Jun He; Pengcheng Liu; Peiyang Yu; Dengxue Liu (Tunnelling and Underground Space Technology, 2024)

Construction and characterization of egg white protein-gallic acid-xanthan gum-based emulsion and oleogel - Yuzhong Yan; Shuling Chen; Le Deng; Yuxuan Duan; Zhaohua Huang; Deming Gong; Guowen Zhang (Food Hydrocolloids, 2024)

Meta-analysis of impacts of microplastics on plant heavy metal(loid) accumulation - Li Chen; Nan Chang; Tianyi Qiu; Na Wang; Qingliang Cui; Shuling Zhao; Fengyu Huang; Hansong Chen; Yi Zeng; Faqin Dong; Linchuan Fang (Environmental Pollution, 2024)

A Three-dimensional Anisotropic Creep Model for Predicting the Time-dependent Deformation of Layered Rock Mass - Shuling Huang; Jinxin Zhang; Xiuli Ding; Gang Han; Peiyang Yu; Xuanting Fan (Rock Mechanics and Rock Engineering, 2024)

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

Effect of heat input on the mechanical properties of welded Q960E ultra-high strength steel butt joints - Shuling Gao; Yanan Yue; Dan Zhang; Ning Li; Yiming Huang; Jiabao Yan; Lijun Yang (Engineering Structures, 2024)

Insights into boosting catalytic hydrogen evolution over Co doping Ru nanoparticles - Hao Wen; Ruofan Shen; Yanyan Liu; Xiaoyan Huang; Shuling Liu; Zhikun Peng; Xianli Wu; Xianji Guo; Erjun Liang; Huiyu Yuan; Baojun Li; Jianchun Jiang (Fuel, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

A weight factor-based backward method for estimating ground stress distribution from the point measurements - Qitao Pei; Cai Wu; Xiuli Ding; Shuling Huang (Bulletin of Engineering Geology and the Environment, 2023)

A comprehensive investigation of engineering geological characteristics of interlayer shear weakness zones embedded within Baihetan hydropower station - Gang Han; Chuanqing Zhang; Hemant Kumar Singh; Shuling Huang; Hui Zhou; Yang Gao (Tunnelling and Underground Space Technology, 2023)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Analytical solution for rock mass bearing plate rheological tests based on a novel viscoelastic combination model - Shuling Huang; Xiuli Ding; Jun He; Shihu Xiong (European Journal of Environmental and Civil Engineering, 2022)

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

Viscoelastic-plastic constitutive model with non-constant parameters for brittle rock under high stress conditions - Shuling Huang; Chuanqing Zhang; Xiuli Ding; Liu Yang (European Journal of Environmental and Civil Engineering, 2022)

Effect of urea feeding on transforming and migrating soil fluorine in a tea garden of hilly region - Hua Long; Yamei Jiang; Chaoqun Li; Shuling Liao; Shuyu Shi; Chunping Huang; Shilin Zhao; Xiaoting Li; Yang Liao (Environmental Geochemistry and Health, 2021)

A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao (Rock Mechanics and Rock Engineering, 2020)

Stability of large underground caverns excavated in layered rock masses with steep dip angles: a case study - Xiuli Ding; Xinqiang Niu; Qitao Pei; Shuling Huang; Yuting Zhang; Cunhui Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Role of mTOR complex in IGF-1 induced neural differentiation of DPSCs - Dan Huang; Shuling Shen; Ming Cai; Lin Jin; Jun Lu; Ke Xu; Jinlong Zhang; Guijuan Feng; Yingzi Hu; Ke Zheng; Xingmei Feng (Journal of Molecular Histology, 2019)

Optimized back analysis method for stress determination based on identification of local stress measurements and its application - Qitao Pei; Xiuli Ding; Yuankun Liu; Bo Lu; Shuling Huang; Jing Fu (Bulletin of Engineering Geology and the Environment, 2019)

SIRT1 was involved in TNF-α-promoted osteogenic differentiation of human DPSCs through Wnt/β-catenin signal - Guijuan Feng; Ke Zheng; Donghui Song; Ke Xu; Dan Huang; Ye Zhang; Peipei Cao; Shuling Shen; Jinlong Zhang; Xingmei Feng; Dongmei Zhang (In Vitro Cellular & Developmental Biology - Animal, 2016)

JAB1 accelerates odontogenic differentiation of dental pulp stem cells - Min Lian; Ye Zhang; Qijie Shen; Jing Xing; Xiaohui Lu; Dan Huang; Peipei Cao; Shuling Shen; Ke Zheng; Jinlong Zhang; Jie Chen; Yi Wang; et al. (Journal of Molecular Histology, 2016)

Residue levels of hexachlorocyclohexane and dichlorodiphenyltrichloroethane in human milk collected from Beijing - Shuling Song; Xiaodong Ma; Ling Tong; Qin Tian; Yi Huang; Shaoquan Yin; Hongbin Sun (Environmental Monitoring and Assessment, 2013)